Fostering self-regulated learning using synchronous or asynchronous digital learning environments: a latent profile analysis of pre-service teachers’ individual differences - Barz, Nathalie; Benick, Manuela; Dörrenbächer-Ulrich, Laura; Perels, Franziska (Frontiers in Education, 2024)
Self-regulated learning (SRL) is positively associated with improved learning achievements during all educational phases. Despite playing an important role in conveying SRL strategies to their students, pre-service often lack knowledge about SRL and imparting it. Therefore, addressing SRL and teaching SRL strategies to students seems relevant to pre-service teacher training. The present study aims to analyze pre-service teachers’ SRL profiles in asynchronous and synchronous digital learning environments and compares their influence on training effectiveness. As part of a pre-post design, a total of N = 141 pre-service teachers participated in the study, and questionnaires on SRL strategy use and an SRL knowledge test were used. A latent profile analysis indicated a three-class solution (low, moderate, high SRL), revealing significant differences regarding SRL strategy use but not for SRL knowledge. These findings enable a person-centered approach to develop digital learning environments and provide insight into specific learner behavior.